Diachronous beginnings of the Anthropocene: The lower bounding surface of anthropogenic deposits. (April 2015) - Edgeworth, Matt; deB Richter, Dan; Waters, Colin; Haff, Peter; Neal, Cath; Price, Simon James
Across a large proportion of Earth's ice-free land surfaces, a solid-phase stratigraphic boundary marks the division between humanly modified ground and natural geological deposits. At its clearest, the division takes the form of an abrupt surface at the base of deposits variously called 'artificial ground', 'anthropogenic ground' or 'archaeological stratigraphy' – which together comprise a distinctive part of the geosphere called the 'archaeosphere'. In other cases the bounding surface is more diffuse, gradational or mixed, due to action of non-human agencies and anthropedogenic forcings. It is alternately conformable and unconformable. Layers above typically contain artificial features, structures, artifacts and other material traces of human activity, in contrast to their relative absence in layers below. A fundamental characteristic of the boundary is that it is diachronous, still being formed and renewed today. In examining the boundary, this paper asks – does it reflect the diachronous onset and development of the Anthropocene itself?